2017
DOI: 10.9734/arrb/2017/38122
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Sociality in Captive Tigers (Panthera tigris)

Abstract: Aims:In this study we assessed the personality and sociality of eight zoo tigers. Place and Duration of the Study: This study was conducted over five months at Le Cornelle Faunistic Park (Valbrembo, BG, Italy). Methodology: A multifaceted approach of observer ratings (rating method) and keeper questionnaires (coding method) was used to produce personality profiles for each tiger. Focal animal behavioural observations allowed the production of time budgets and enclosure usage for each animal. Sociality was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The results obtained in the present study have shown that the keepers knew every penguin very well, and they were able to consistently evaluate their behavioral characteristics [23,24]. This data is useful to underline the importance of the professional figure of the zookeeper, which has prominent responsibilities in the daily welfare of the animals [29,38].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The results obtained in the present study have shown that the keepers knew every penguin very well, and they were able to consistently evaluate their behavioral characteristics [23,24]. This data is useful to underline the importance of the professional figure of the zookeeper, which has prominent responsibilities in the daily welfare of the animals [29,38].…”
Section: Discussionmentioning
confidence: 52%
“…The first part of the questionnaire presented some questions related to keeper’s work, to their interests for the birds (in particular penguins), and to the perception that they have of the personality influence on the animals’ behavior and health. In order to describe penguin behavioral and personality aspects, in the second part of the questionnaire were included 31 adjectives (Table S2), which were rated on a scale of 1 (trait never exhibited) to 12 (trait always exhibited), depending on how well they described each penguin [23,24]. Two keepers completed the questionnaires for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…A sociogram was developed to illustrate the frequency of inter-Observations of stereotypical behaviour were low or non-existent in all of the subjects except one. Victor was observed pacing on multiple occasions, which is the most common type of stereotypy in bears [19,20]. In the previous study using camera traps Quintavalle Pastorino., et al [8] study found that stereotypical behaviours were the least observed category.…”
Section: Social Interactionmentioning
confidence: 98%
“…For example, among reintroduced African lions, the sub-adults are more likely 272 to be alert than adults [18]. Similarly, tigers tend to be less aggressive and more friendly as 273 they age [19]. However, other studies found no significance of age on personality dimensions 274 of African lions [14] or cheetahs [25].…”
Section: Factors Influencing the Personality Dimensions And Stress Physiology Of African Lions 249mentioning
confidence: 99%
“…In captivity, the welfare of these lions is a considerable concern, as it is difficult to mimic their wide-ranging natural habitat [13]. A variety of behavioural tests and checklists have been developed in the past decade to help identify traits of wellbeing and the personalities among big cats (Vaz et al, in press); these tests and checklists have been used for lions [14][15][16][17][18], tigers [19][20][21], jaguars [22], cheetahs [23][24][25][26], snow leopards [27,28], and in particular the Asiatic lion personality [15,17] and African lion personality [14,16,18]. Similarly, studies have tried to understand the stress physiology and variation in GCs for lions [29][30][31].…”
Section: Introductionmentioning
confidence: 99%